ANALISIS PEMILIHAN MEDIA PROMOSI PADA PERUSAHAAN JASA TERAPI - Stefani Stefani (Universitas Bunda Mulia, 2017)
One of the most important elements for the company is to introduce their products (services) to prospective customers. Hypnosis For Healing is a company engaged in services. One key to the success of this company especially to attract clients is through the promotion of this company so that it is known by many more people. It requires the selection of appropriate media in accordance with the consideration of criteria such as low cost, wide coverage. These service companies require appropriate promotional media. This study aims to find a suitable promotional media on HFH company. The research was conducted in the end of 2010. The analytical tool used is Analytical /various alternatives based on several criteria. The results of this study show that the internet is a major media as a promotional tool to introduce to the general public. Keywords : Methods of Analytical Hierarchy Process (AHP), Promotional media.